Meningkatkan Budaya Literasi Siswa SD Swasta HKBP Sidorame Melalui Perkenalan Adat dan Budaya Indonesia dan Republik Ceko - Saragih, Elza Leyli Lisnora; Manurung, Rolan; Siagian, Beslina Afriani; Simanjuntak, Harlen; Sitohang, Tigor (UKInstitute, 2022)
The purpose of this community service is to increase knowledge and experience regarding the language, customs and culture of the Czech Republic, which of course will be very different from Indonesia. The method used in this service is the method of preparation, implementation, and evaluation. The activity was carried out using the Active, Creative, Effective, and Fun Learning model so that elementary school students felt more comfortable and less tense in following the explanations of students from the Czech Republic. Community Service is held for 2 meetings with a time of 3 hours 1 meeting so that students get to know FKIP lecturers and students as well as students from the Czech Republic so that students at SD HKBP Sidoprame Medan are more free to ask questions and easily understand the culture and customs of the Czech Republic. The evaluation of the introduction of Indonesian and Czech cultural customs got good or satisfactory results, so that this service had a positive impact on the students of SD HKBP Sidorame Medan. This is because after listening to direct explanations from CULS students about the education system in the Czech Republic, students become more enthusiastic in learning so they can study higher in the Czech Republic. Students of SD HKBP Sidorame Medan also have a better understanding of tolerance and have high empathy such as being easy to help and willing to listen to others